Let \(A(t) = 3- 2t^2 + 4^t\). Find \(A(2) - A(1)\).
I think this was answered in your previous post....but will check answer
A(2) = 3 - 2 (2)^2 + 42
A(1) = 3 - 2(12) +41
11-5 = 6
Thank you for asking the question. :))
But try not to repost stuff.
Especially if they are still on the front page and have been answered.
If they are answered incorrectly, just leave a note and hopefully someone will correct it.
Reposting will sometimes cause people to waste time answering questions that have already been answered in another post.